Newsprint-grade Pulp Furnishes from Plantation Grown Eucalyptus in Admixture with Bagasse - Dhawan, Rita; Karira, B. G. (Indian Forester, 1992)
The plantation grown Eucalyptus tereticornis is being widely used for the production of high-yield pulp component of newsprint furnishes. Present investigations have been carried out to optimize the proportions of high yield pulps, viz, Chemi-mechanical/Refiner mechanical pulps from E. tereticornis in admixture with high yield, viz, semi-chemical pulp from bagasse for making newsprint grade pulp furnishes. Results reveal that newsprint furnishes of satisfactory strength properties and improved brightness and opaci1y could be produced besides conserving the valuable Eucalyptus resources.